Status of Adverse Drug Reaction Reporting by Health Care Professionals of Delhi - P, Amrita; P.S, Simar; K, Vineet (Indian Journal of Pharmacy Practice)
Objective: To evaluate the awareness of health care professionals (HCPs) regarding Pharmacovigilance, adverse drug reactions (ADRs) and it's reporting. Method: Aself-structured questionnaire was delivered by hand to a sample of 590 HCPs in Delhi. The filled questionnaire was collected on the same day. Result: The Response rate of this survey was 63.73%. The HCPs were Physicians (32.98%), pharmacists (39.36%) and nurses (27.66%). Only 58.24% HCPs were aware of the broad meaning of the Pharmacovigilance and ADR. Majority of HCPs (90.43%) felt that ADR monitoring is essential. Though 45.48% HCPs reported the ADRs encountered by them just 3.19% HCPs had faint information that reporting can be done at National Monitoring Centre (NMC) and/or Regional monitoring centres (RMC). All India Institute of Medical Sciences (AIIMS) and Lady Hardinge Medical College (LHMC) as ADR monitoring centres of Delhi were known to only 5.85% HCPs. Out of these, only 1.86% HCPs had the phone number and/or address of these centres. It indicates that the ADR reporting is done by HCPs at places other than NMC and RMC. Conclusion: Reporting of ADRs by HCPs is poor. Among the HCPs, the knowledge, skill & attitude towards pharmacovigilance and ADR reporting was highest of physicians followed by nurses and then pharmacists. Education and training is essential to increase ADR reporting rate by HCPs.
Keywords: Health Care Professionals; ADRs; Pharmacovigilance